Factors affecting good corporate governance at pt. Lotte shopping Indonesia Center Point Medan - Irna Triannur Lubis (Enrichment : Journal of Management, 2023)
This study aims to determine the effect of the implementation of the Accounting Information System, Internal Control, and Internal Audit on Good Corporate Governance at PT Lotte Shopping Indonesia Center Point Medan. This research uses quantitative data types and the data source is the primary data obtained from PT Lotte Shopping Indonesia Center Point Medan. From the population, purposive sampling was taken and a sample of 51 employees was drawn. Research variables consist of accounting information systems, internal control and good corporate governance. The sampling technique of this study used several specific criteria. The results of the study stated that the implementation of the Accounting Information System and Internal Control had a significant effect on Good Corporate Governance.